Modelagem de conversores estáticos CC-CC em modo de condução contínua - Costa, Lucas (2022)
Static converters are eletronic devices capable of modifying voltage and current levels. They are used in numerous applications where there is a need to couple two electrical systems that operate at different voltage and current levels. This work presents a methodology for modeling static DC-DC converters, where the buck, boost and buck-boost converters were studied. Using a switching network model, common to the three converters, it was found: an average model for large signals, which represents the average value of the quantities involved, using controlled voltage and current sources; an averaging model for small signals, in the frequency and time domains, which is linear for small variations around an operating point; and a model for dual loop control, that is, control of the output voltage and inductor current. The models found were validated through simulations in the PSIM software. The results found were satisfactory, that is, the models developed (equations) were similar to the switched models (simulated circuit). Thus, it is understood that the study methodology adopted proved to be coherent and the results obtained here can be used for the design of DC-DC converters.